The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.celrep.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA PURPL Suppresses Basal p53 Levels and Promotes Tumorigenicity in Colorectal Cancer

Abstract: SUMMARY Basal p53 levels are tightly suppressed under normal conditions. Disrupting this regulation results in elevated p53 levels to induce cell cycle arrest, apoptosis and tumor suppression. Here, we report the suppression of basal p53 levels by a nuclear, p53-regulated long noncoding RNA that we termed PURPL (p53 upregulated regulator of p53 levels). Targeted depletion of PURPL in colorectal cancer cells results in elevated basal p53 levels and induces growth defects in cell culture and in mouse xenografts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
125
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 70 publications
(100 reference statements)
10
125
2
Order By: Relevance
“…In short, subcutaneous tumor xenografting was performed by injecting the right flank of nude mice with 1×10 7 cells that had been transfected with the indicated plasmids. After 4 weeks, the mice were sacrificed, and …”
Section: Tumor Xenograft Modelmentioning
confidence: 99%
“…In short, subcutaneous tumor xenografting was performed by injecting the right flank of nude mice with 1×10 7 cells that had been transfected with the indicated plasmids. After 4 weeks, the mice were sacrificed, and …”
Section: Tumor Xenograft Modelmentioning
confidence: 99%
“…As expected, we found that the expression of PRLH1 increased nearly up to eightfold in SK-HEP-1 cells, while remaining unchanged in HuH-7 cells after knockdown of p53 by siRNA ( Fig 1F). Notably, the knockout of p53 in HepG2 cells led to a remarkable decrease in the expression of the known p53-activated lncRNA PURPL [40] and a significant increase in the expression of other three lncRNAs (AC073236.3, RP11-81H3.2, and RP11-328N19.1) displayed in Fig 1C (Appendix Fig S1G), indicating that these three lncRNAs were also repressed directly or indirectly by wild-type p53. Notably, the knockout of p53 in HepG2 cells led to a remarkable decrease in the expression of the known p53-activated lncRNA PURPL [40] and a significant increase in the expression of other three lncRNAs (AC073236.3, RP11-81H3.2, and RP11-328N19.1) displayed in Fig 1C (Appendix Fig S1G), indicating that these three lncRNAs were also repressed directly or indirectly by wild-type p53.…”
Section: Prlh1 Is An Erv-9 Ltr Lncrna Regulated By P53mentioning
confidence: 96%
“…In a recent issue of Cell Reports, Li et al (22) identified and functionally characterized the p53-regulated lncRNA PURPL in colorectal cancer. PURPL was strongly induced by DNA damage and was predominant in nuclear.…”
mentioning
confidence: 99%
“…By RNA pulldown and mass spectrometry, Li et al (22) found strong interaction between PURPL and MYBBP1A, a protein that stabilizes p53. In light of the authors’ result that loss of PURPL increased p53 levels, they proposed that loss of PURPL freed up MYBBP1A, enabling it to bind and increase p53 stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation